Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi Bali, Jambi, Papua Barat, Dan Papua Tengah Tahun 2023/2024 - Rosyani, Perani; Gisma Ripan, Fitrah; Bunga, Azaria; Nur Hafsari, Lintang; Saputro, Bagus (CV. Shofanah Media Berkah, 2024)
The study aims to analyze the distribution of school principals and teachers based on age groups in the provinces of Bali, Jambi, West Papua, and Central Papua. This research employs a descriptive quantitative approach using data sourced from the 2023/2024 BPS reports and related academic journals. The findings indicate that the age distribution of educators varies across provinces. Bali and Jambi show higher mean and median ages, indicating a dominance of experienced educators. On the other hand, West Papua and Central Papua have lower mean and median ages, suggesting a predominance of younger educators. These findings offer a better understanding of the age composition of educators in each province and highlight the importance of educational policy planning tailored to the demographic conditions of each region. This data is expected to serve as a foundation for stakeholders in enhancing the quality and sustainability of education in Indonesia.